Natural Language Processing with Java - Second Edition - AshishSingh Bhatia; Richard M. Reese (Packt Publishing, 2018)
This book, "Natural Language Processing with Java," is your practical guide to mastering NLP concepts and techniques using Java. You'll explore how to process, analyze, and understand language with powerful Java frameworks such as CoreNLP and OpenNLP, implementing tasks from tokenization to advanced neural network models. Perfect for those eager to deepen their Java and NLP expertise, this resource delivers actionable skills and insights.What this Book will help me doMaster fundamental NLP concepts and various NLP tasks, enhancing your understanding of the field.Gain hands-on experience with Java-based NLP libraries for practical implementation of language processing.Learn techniques for natural language tokenization, parsing, and identifying relationships in text.Apply machine learning methods like topic modeling, summarization, and dialog systems to language data.Build real-world NLP applications such as chatbots and machine translation systems using Java.Author(s)Richard M. Reese brings a wealth of technical expertise as a software developer, instructor, and author. With extensive experience in Java and a passion for natural language processing, he delivers clear and actionable strategies to simplify complex topics for readers to apply. His approachable teaching style ensures learners of Java and NLP gain confidence and proficiency in tackling real-world problems.Who is it for?This book is ideal for software developers, machine learning enthusiasts, and data scientists who are looking to deepen their expertise in natural language processing using Java. If you are familiar with Java and eager to develop NLP applications, this book will provide you the knowledge and tools necessary to succeed. Additionally, it's suited for professionals seeking methods to analyze textual data effectively to derive insights. Whether you're advanced or just comfortable with the basics, if you have an interest in languages and technology, this book is for you.